A STUDY ON THE COHESION USED IN THE EXPOSITORY ESSAY OF ENGLISH LITERATURE STUDENTS - HIDAYANTO, RIYAN (Jurnal Ilmiah Mahasiswa FIB, 2015)
Key Words: cohesive device, expository essays, grammatical cohesion, lexical cohesion In this study the researcher is interested in conducting a research on cohesive devices found in expository essays written by third semester students of English Literature. There are two proposed problems: (1) what are the types of cohesive device used by the third semester students of English Literature in their expository essays, and (2) what are the dominant types of cohesive device used by the third semester students of English Literature in their expository essays. To answer the problem of study the writer employs two main theories, those are  theory of grammatical cohesion proposed by Halliday and Hasan (1976) and theory of lexicalcohesion by Renkema (2004). This research used qualitative approach because the data were explained in the form of description rather than numeral. Besides, the research was conducted through document analysis because the data were in the form of phrases or sentences containing cohesive devices derived from the expository esssays. The data source inthis thesis are 7 essays written by the students of the third semester of English Literature. These sample are taken based on purposive sampling, the criterion of which is the highest graded essay in midterm test from each class.  Based on the result of the analysis, it is revealed that third semester students of English Literature could employ all the four types of grammatical cohesion to build cohesion in their expository essays: reference (personal, demonstrative, comparative), subtitution (nominal), ellipsis (nominal, verbal, clausal), conjunction (additive, adversative, causal, temporal). In regard to grammatical cohesion, the most commonly used type is reference (66%), while in lexical cohesion, the mostfrequently used type is repetition (59%).  It is suggested to the next researchers who want to conduct study with the same field as the recent one to use other objects of study such as introduction in thesis. Besides, the writer also suggested the next researchers to investigate the corelation between the usage of cohesive devices with the clarity or persuasive quality in certain kinds of writing.